Teledermatology: Comparison of Store-and-Forward Versus Live Interactive Video Conferencing. - Brinker, Titus Josef; Hekler, Achim; Von Kalle, Christof; Schadendorf, Dirk; Esser, Stefan; Zacher, Martina T.; Sondermann, Wiebke; Grabe, Niels; Steeb, Theresa; Utikal, Jochen Sven; French, Lars E.; Enk, Alexander H.; et al. (Journal of Medical Internet Research, 2018)
A decreasing number of dermatologists and an increasing number of patients in Western countries have led to a relative lack of clinicians providing expert dermatologic care. This, in turn, has prolonged wait times for patients to be examined, putting them at risk. Store-and-forward teledermatology improves patient access to dermatologists through asynchronous consultations, reducing wait times to obtain a consultation. However, live video conferencing as a synchronous service is also frequently used by practitioners because it allows immediate interaction between patient and physician. This raises the question of which of the two approaches is superior in terms of quality of care and convenience. There are pros and cons for each in terms of technical requirements and features. This viewpoint compares the two techniques based on a literature review and a clinical perspective to help dermatologists assess the value of teledermatology and determine which techniques would be valuable in their practice.
EVALuna2:156580